WORKSHOP ON WRITING OF SCIENTIFIC JOURNAL ARTICLES FOR TEACHERS OF SMA NEGERI 1 PALANGKA RAYA - Yossita Wisman; Bernisa; Karelius; Muhammad Rifky; Siswo (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2020)
Nowadays, in order to obtain promotion from the rank of Group IVa to IVb, a teacher is required to provide scientific works. However, according to Ministerial Decree No. 16/2009, scientific work has become a promotion requirement from Group IIIb to IIIc; thus, the teacher must have the ability to produce scientific papers. This community service was aimed to provide knowledge and skills for teachers of SMAN 1 Palangka Raya to produce and publish scientific papers in the ISSN local journals. Participants in the activity generally consisted of junior teachers and by using training methods in the form of lectures and questions and answers, demonstrations and practice.